2017
DOI: 10.7205/milmed-d-16-00368
|View full text |Cite
|
Sign up to set email alerts
|

Multispecialty Synchronous Telehealth Utilization and Patient Satisfaction Within Regional Health Command Europe: A Readiness and Recapture System for Health

Abstract: Clinic utilization varied between specialties as well as whether a specialty-trained patient presenter was preferred. This robust multispecialty synchronous telehealth experience provides insight into both specialty-specific utilization and patient satisfaction which may aid regional medical centers recognizing avenues for specialty-specific telehealth initiatives.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
18
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 23 publications
(21 citation statements)
references
References 6 publications
1
18
0
Order By: Relevance
“…Participant 6 DISCUSSION Clients in this study reported both benefits and barriers to telehealth, with overall benefits outweighing barriers. This replicates previous research findings of an overall positive client experience in which reported benefits outweighed barriers (Chou et al, 2013;Eikelboom & Atlas, 2005;Levy et al, 2015;Polinski et al, 2015;Waibel et al, 2017;Young et al, 2011). However, even when clients report an overall benefit from telehealth service delivery, their opinions and preference for telehealth may not be entirely positive (Sorenson, 2008).…”
Section: Close-ended Responsessupporting
confidence: 73%
See 1 more Smart Citation
“…Participant 6 DISCUSSION Clients in this study reported both benefits and barriers to telehealth, with overall benefits outweighing barriers. This replicates previous research findings of an overall positive client experience in which reported benefits outweighed barriers (Chou et al, 2013;Eikelboom & Atlas, 2005;Levy et al, 2015;Polinski et al, 2015;Waibel et al, 2017;Young et al, 2011). However, even when clients report an overall benefit from telehealth service delivery, their opinions and preference for telehealth may not be entirely positive (Sorenson, 2008).…”
Section: Close-ended Responsessupporting
confidence: 73%
“…Past survey research indicated clients are satisfied with telehealth experiences (Chou et al, 2013;Eikelboom & Atlas, 2005;Levy et al, 2015;Polinski et al, 2015;Waibel, Cain, Hall, & Keen, 2017;Young et al, 2011). However, client preference for telehealth or inperson service delivery varies.…”
Section: Literature Reviewmentioning
confidence: 99%
“…(2017) 24 USA Videoconference 10 100% patients were satisfied Spinal Cord Injuries follow up NR Waibel KH et al. (2017) 25 Germany Smartphone application 5 Average satisfaction score of 4.7 out of 5 Frozen shoulder NR Buvik A et al. (2019) 26 Norway Videoconference 199 99% patients were satisfied Orthopaedic new referred, follow-up after surgery, trauma or chronic disorders NR Sinha N et al.…”
Section: Discussionmentioning
confidence: 99%
“…Our findings of high patient satisfaction are consistent with the reports of prior studies in the existing telehealth literature. For example, in another study of multispecialty telehealth delivery, an average of 4.8/5 on the Likert scale was reported for patient satisfaction (11). Thus, it is not surprising that a high number of patients in our study said they would recommend video visits in the future.…”
Section: Discussionmentioning
confidence: 63%